Chemotactic activity derived from interaction of factors D and B of the properdin pathway with cobra venom factor or C3B. - Ruddy, S (1975)
Interaction of D (the activated form of D) and B, factors of the properdin pathway, with C3b (the major cleavage fragment of C3) generates a convertase, C3B, which cleaves C3 and initiates the terminal complement sequence C5-C9. A functionally analogous more stable C3 convertase, CoVFB, ir formed by substituting cobra venom factor (CoVF) for C3b. Mixtures of highly purified CoVF, B, and D were chemotactic for human neutrophil polymorphonuclear leukocytes as assessed in Boyden chambers either by microscopic enumeration of migrating cells or by counting of 51Cr-labeled cells. Control mixtures containing CoVF, B, and D, reacted in the absence of Mg++, were hemolytically inactive and devoid of chemotactic activity. Over a range of doses, the chemotactic activity of mixtures yielding CoVFB correlated with their hemolytic activity. Pretreatment of neutrophils with mixtures containing CoVFB rendered them unresponsive to subsequent chemotactic stimulation by kallikrein of C5a, indicating cross-deactivation to other chemotactic factors. Similar neutrophil deactivation occurred after exposure to a mixture of C3b, B, and D in which C3B was formed; with short incubation times and high cell concentration C3B also exhibited some chemotactic activity. The chemotactic activity of C3B and CoVFB is an example of a biologic function arising from interactions among factors of the properdin pathway per se, as distinguished from the capacity of this pathway to activate C3 and the terminal complement sequence.